Miłość kończąca się na sali sądowej. Relacje małżeńskie w procesie rozwodowym - Ruszkiewicz, Marta (Człowiek i Społeczeństwo, 2021)
This article analyses the components of love and the stages of a love relationship in relation to the increasingly common phenomenon of divorce in society. The author underlines that the reason of filing for divorce may be the further development of love and – more specifically – the decline of passion and intimacy, of which the spouses may not be aware. Qualitative changes in love surprise the spouses and cause dissatisfaction. The availability and popularity of divorces, in turn, induce the spouses to resort to such tools. According to the author, an increase in the social awareness in this matter could make it possible to avoid many divorce processes.